Sustainable land use and green ecology: A case from the Beijing 2022 Winter Olympics venue legacy - Wang, Weihao; Liu, Zhaoran; Bu, Te; Jiao, Fangqian (Frontiers in Environmental Science, 2023)
According to the Olympic Charter, the construction of new permanent venues or infrastructure for the purposes of the organization of the Olympics shall only be considered on the basis of sustainable legacy plans. However, as time passes, the Olympic legacies grow increasingly unsustainable and create conflicts between humans and nature. This perspective examined the spatial distribution of the Beijing 2022 Winter Olympics venue legacy. We presented a spatial assessment of Olympic venues’ legacy experience in terms of construction and and sustainability. The findings indicate that the Beijing 2022 Winter Olympics venues incorporated sustainable land management and green ecology concepts from the Olympic Movement, and that the legacy could serve as an example for future development of Olympic infrastructure, natural sites, and resource management.